Magyar magánjogászok a német jog hatásáról és a jogfosztásról (1920–1944) - Krausz, Bernadett (Díké - A Márkus Dezső Összehasonlító Jogtörténeti Kutatócsoport folyóirata, 2021)
The study aims to discover the Hungarian relations to the Academy for German Law between 1920–1944 and the influence of German law to Hungarian Civil law. It also analyses the reaction of Hungarian jurists to the right restrictions and deprivations of the Horthy era concerning Civil law, whether they welcomed or criticized them and more importantly, if they spoke about them at all publicly. I examined the legal papers that were published in the subject period, namely the Journal of Law, Civil Law and Hungarian Legal Review in order to seek answers.